Conditioning of nurses’ work in infectious diseases wards in association with the COVID-19 pandemic - Sierpińska, Lidia; Kopeć, Justyna (Journal of Education, Health and Sport, 2021)
Introduction Infectious diseases, due to their specificity and rapid spread, require a special, individual approach, not only to the treatment, but also to the protection of medical staff against infection. Objective: The aim of the study is recognition of the conditioning of work of nurses in hospitals dedicated to COVID-19, at the time of pandemic. Materials and Method The study included 100 nursing staff - 78 females (78%) and 22 males (22%) employed in Polish hospitals dedicated to care of patients with COVID-19 by virtue of the Minister of Health [5]. The research material was collected during the period from 15 January 2021 - do 12 February 2021. The largest group in the study was aged under 30 (32%), and similarly those aged 31 - 40 (31%). The respondents aged 41 - 50 constituted 21% of the nursing staff examined. The smallest group of nurses was aged over 60 (16%). The largest number of the nursing staff lived in urban areas (78%), whereas the reminder in rural areas (22%). The study was conducted by the method of a diagnostic survey, using a questionnaire technique, while the research tool was an author-constructed questionnaire designed for the purpose of the presented study. Conclusions In dedicated hospitals it is necessary to optimize the equipment in the ward indispensable for care of patients with COVID-19, which would improve the working conditions of nurses. It is advisable to adjust the employment of nurses to the demand for nursing care of patients seriously ill with COVID-19, treated in dedicated hospitals. In infectious diseases hospitals, in-hospital training courses should be intensified concerning the OSH and sanitary-hygienic principles in care of patients with COVID-19, because ¼ of the examined nurses indicated such a need.